MERLIN: The German-French Methane Remote Lidar Mission - Kiemle, Christoph; Ehret, Gerhard; Bousquet, Philippe; Fix, Andreas; Wirth, Martin (2016)
Methane is the third most important greenhouse gas in the atmosphere after water vapor and carbon dioxide, and responsible for about 20% of the warming induced by long-lived greenhouse gases since pre-industrial times. Concentrations of atmospheric methane have tripled since then, arguably the largest global change in atmospheric composition caused by human beings. Increases leveled off abruptly between 1990 and 2005, and then started to rise sharply again, for reasons not yet well determined. This is mainly due to a lack of accurate and global observations of methane for quantifying biosphere-atmosphere exchange processes and related climate feedbacks. Space-based missions using lidar as an active remote sensor have potential to complement the current greenhouse gas observing systems by closing observational gaps, e.g., over subarctic permafrost and tropical wetlands, where in-situ and passive remote sensing techniques have difficulties in providing robust flux estimates. Furthermore, the lidar data are expected to have a principally low bias, not influenced by aerosol layers or thin cirrus clouds. Consequently, a “Methane Remote Lidar Mission” (MERLIN) was proposed by the German and French space agencies DLR and CNES. MERLIN has successfully completed Phase B; launch is foreseen in 2020. Primary objective is to provide accurate global observations of methane concentration gradients for inverse numerical models in order to better quantify regional fluxes. Spin-off products are global cloud cover and canopy height. Wetlands, the most important natural methane sources, show at the same time the largest uncertainty and variability. Wetlands are abundant in remote tropical and high-latitude regions, challenging the deployment of in-situ instrumentation. On the other hand, space-borne passive remote sensing is hindered in the tropics by frequently occurring deep convection, and blind at high latitudes due to lack of sunlight. In the tropics it is expected that MERLIN will measure in between clouds, thanks to its ...